Multicomponent pattern and biological activities of seven Asphodeline taxa: potential sources of natural-functional ingredients for bioactive formulations. (1st January 2017) - Locatelli, Marcello; Zengin, Gokhan; Uysal, Ahmet; Carradori, Simone; De Luca, Elisa; Bellagamba, Giuseppe; Aktumsek, Abdurrahman; Lazarova, Irina
Abstract: The current study was carried out to evaluate multicomponent pattern, biological and enzymatic activities of seven Asphodeline taxa root extracts as useful ingredients, due to the fact that these plants are commonly used as traditional food supplements in Turkish regions. The extracts were characterized for free anthraquinones and phenolics to obtain a specific chemical fingerprint useful for quality control. These analyzes were coupled to biological and enzymatic activities in order to obtain comprehensive information of the natural product. Free anthraquinones and phenolics were determined using validated HPLC-PDA methods. Antioxidant properties were determined by different procedures including free radical scavenging, reducing power, phosphomolybdenum and metal chelating assays. Ames assay was performed to evaluate mutagenic/antimutagenic properties. Enzyme inhibitory activities were tested against cholinesterase, tyrosinase, α-amylase and α-glucosidase. From the herein reported results, Asphodeline could be valuable for the production of bioactive products or food supplements for cosmetic and pharmaceutical industries.